GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SUMBER DAYA MANUSIA DI SEKOLAH - ismail, M. Jen Ismail (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2021)
This research is a qualitative descriptive study about the transformational leadership style of principals in improving the quality of human resources in schools. The location of this research is SMP Negeri 1 Tomini. So the description in this study departs from the problem of how the principal's transformational leadership style in improving the quality of human resources at SMP Negeri 1 Tomini? And what are the opportunities and challenges of the principal's transformational leadership at SMP Negeri 1 Tomini? This research uses qualitative research. The data collection techniques that the writer did, namely through observation, interviews, and documentation. Meanwhile, the data analysis techniques used in this study were data reduction, data presentation, and conclusion drawing. The results of the study found a concept, that the principal's transformational leadership style in improving the quality of human resources at SMP Negeri 1 Tomini is that the principal improves the quality of teachers, staff and students not only through education but provides the widest possible opportunity for employees to participate in activities. outside of school such as seminars and workshops to increase their knowledge. Then develop the skills of students such as extracurricular activities. In addition, it also complements school facilities because it can increase creativity in active teaching and learning. Opportunities and challenges for the transformational leadership of the principal at SMP Negeri 1 Tomini, namely by delivering the program consistently and transparently, and 80% of the teachers and staff at the school are adequate and have an undergraduate level and are temporarily continuing their master's degree. Then the facilities and infrastructure are very supportive and when problems occur at school, such as learning problems and misunderstandings (personality with a bit of ego) between teachers and staff to anticipate this, the principal gives limits and warnings at the evaluation meeting which is held every three months.